Virtual Surgical Planning in Free Tissue Transfer for Orbito-Maxillary Reconstruction - Cho, Min-Jeong; Hanasono, Matthew M. (Seminars in Plastic Surgery, 2022)
Since its introduction, virtual surgical planning (VSP) has been rapidly adopted as a part of reconstructive surgeon's armamentarium. VSP allows reconstructive surgeons to simulate resection, plan osteotomies, and design custom plates. These unique advantages have been especially beneficial for head and neck reconstructive surgeons as there is small room for error and high technical demand in head and neck reconstruction. Despite its popularity, most surgeons have limited experience in using VSP for orbito-maxillary reconstruction as tumors that involve the midface are relatively rare compared with other head and neck oncologic defects. In our institution, we routinely use VSP for orbito-maxillary reconstruction using free fibula flap to provide support for orbit, to restore normal dental occlusion, and to restore midface projection. In this chapter, we will discuss the role of virtual surgical planning and our algorithmic approach of performing orbito-maxillary reconstruction using free tissue transfer.
Keywords: orbito-maxillary reconstruction; fibula flap; virtual surgical planning; VSP; 3D printing; CAD/CAM; computer-aided design and computer-aided manufacturing